Effect of monocytes/macrophages on the early osteogenic differentiation of hBMSCs. (6th March 2012) - Pirraco, R. P.; Reis, R. L.; Marques, A. P.
Abstract Heterotypic cell interactions are essential for the homeostasis of bone tissue, in particular the widely studied interaction between osteoblasts and osteoclasts. Closely related with osteoclasts are monocytes/macrophages. These have been shown to produce osteogenic factors, e.g. BMP‐2, which plays a key role in bone metabolism. However, the mechanisms through which monocytes/macrophages interact with osteoblasts are still elusive. The aim of this work was to assess the influence of human peripheral blood monocytes/macrophages over the early osteogenic differentiation of human bone marrow stromal cells (hBMSCs) in the presence of dexamethasone‐supplemented medium. The co‐cultures were performed using porous transwells that allowed the interaction between both cell types through the production of paracrine factors. The potential effect of BMP‐2 produced by monocytes/macrophages was addressed by adding an anti‐BMP‐2 antibody to the co‐cultures. hBMSCs cultured in the presence of monocytes/macrophages had a higher proliferation rate than hBMSCs monocultures. The quantification of early osteogenic marker alkaline phosphatase (ALP) revealed higher activity of this enzyme in cells in the co‐culture throughout the time of culture. Both of these effects were inhibited by adding an anti‐BMP‐2 antibody to the cultures. Moreover, qRT–PCR for osteocalcin and osteopontin transcripts showed overexpression of both markers. Once again, the effect of monocytes/macrophages over hBMSC osteogenic differentiation was completely inhibited in the co‐cultures by blocking BMP‐2. The present report confirmed that monocytes/macrophages produce BMP‐2, which promotes osteogenic differentiation and proliferation of hBMSCs cumulatively to dexamethasone‐supplemented medium. This potentially implies that monocyte/macrophages play a stronger role in bone homeostasis than so far supposed. Copyright © 2012 John Wiley & Sons, Ltd.